The relationship between consumer-perceived athlete celebrity in product endorsement and purchase intentions - Ang, Hui Ni, author; Abu Bakar Abdul Hamid, supervisor; Fakulti Pengurusan dan Pembangunan Sumber Manusia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2011)
Project Paper (Sarjana Muda Pengurusan (Pemasaran)) - Universiti Teknologi Malaysia, 2011